Автоматизация процессов управления дождеванием - Леви, Л. И.; Правдюк, Д. М. (Видавництво Львівської політехніки, 2011)
This paper describes the process of sprinkling machines. Proposed a method for automating the process of sprinkling management.
Keywords: automation of control processes; sprinkling system; artificial neural network; precision agriculture; sprinkling dosage